Role for Industry in the Development of Degraded forests: a Need for Change in Policy - Rawat, J. K. (Indian Forester, 1994)
National Forest Policy of 1988 prohibits raising of captive plantations by industry on forest lands. A change in this policy is recommended. The forest based industries have resources which can be harnessed to develop degraded forests by giving them long term lease over these areas where they can grow wood for their factories. Problems and objections likely to arise due to the proposed shift in policy and the ways to safeguard interests of the society and the nation have been discussed.